Strategic management implementation of the cooperatives, industry and trade department in the development of micro small and medium business in Situbondo Regency - Rasidi, Moh.; Yoga , M. Yoga Pratama; Taufiqurrahman, Taufiqurrahman; Arisandi , M. Iqbal (Institute of Computer Science (IOCS), 2025)
In Situbondo Regency, there are several problems related to the development of micro, small and medium business. Therefore, the Cooperatives, Industry and Trade Department needs to formulate strategic efforts in developing micro, small and medium business in Situbondo Regency. Strategic efforts that can be made by the Cooperatives, Industry and Trade Department in developing micro, small and medium business are through a strategic management approach. The purpose of this study is to determine the application of strategic management of the Cooperatives, Industry and Trade Department in the development of micro, small and medium business in Situbondo Regency. The method used in this research is a qualitative research method, as a method that aims to understand phenomena such as behavior, perception, motivation, actions, and the like experienced by society. The results of the study show that the implementation of strategic management by the Cooperatives, Industry and Trade Department of Situbondo Regency to support the development of micro, small and medium business consists of 1) formulation which includes strategic budget planning and main pillars, 2) implementation which includes training and mentoring, facilities and capital, promotion and marketing, and 3) evaluation which includes performance measurement, impact of obstacles and challenges.